Right ventricular thrombus and pulmonary embolism after infliximab therapy for ulcerative colitis. Issue 6 (28th June 2021) - Ogilvie, Jennifer Ann; Iraqi, Ahmed; Haas, Christopher; Bharaj, Raman
Abstract : Infliximab, an antitumour necrosis factor alpha (TNF-alpha)agent, is a cornerstone of treatment of inflammatory bowel disease with a favourable and well-tolerated side effect profile. While the majority of side effects associated with infliximab have been well established, the pathophysiology of infliximab-associated thrombosis remains controversial and poorly defined. We present a case of a young woman with ulcerative colitis who presented with a right ventricular thrombus and bilateral pulmonary emboli after initiation of infliximab and was subsequently found to have underlying factor V Leiden and prothrombin gene mutation. Clinicians should be aware of this potential adverse event associated with anti-TNF agents, especially in individuals with predisposing prothrombotic mutations such as factor V Leiden or prothrombin gene mutation.